Manajemen Asuhan Kebidanan Berkelanjutan Pada Balita “F” Usia 22 Bulan Dengan Gizi Kurang Di Praktik Mandiri Bidan Hj. nuryati Tanggal 23 Juni - 04 Agustus 2022: Continuous Midwifery Care Management on a Toddler with the Case of Malnutrition at Independent Midwifery Service of Hj. Nuryati on 23 Juni - 04 Agustus 2022 - Rizky Adzania; Ferawati Taherong; Firdayanti (Jurnal Midwifery, 2023)
Introduction Malnutrition in toddlers refers to a condition of wasing where the weight of babies is not in line with their age and height. Several attributes have been metioned as the major causes of this malnutrition and those include direct and indirect factors. Purpose This case study research aims to implement sustainable midwifery care management for children under five at the Independent Practice of Midwife Hj. Nuryati. Method The study was conducted by using Varney's 7 Steps. Result The patient “F” was assessed, and his medical condition was monitored regularly especially her growth development. In addition, counselings were also given to the patient’s parents, particularly related to nutrition and balanced diet, personal hygiene, and caring management. Moreover, pre-screening development was also administered to the patient to prevent further complications for the patient. Conclusion In this research, 6 visits were conducted to the patient where the patient’s weight was apparent to increase gradually from a mere 8.6 kg to approximately 9.5 kg. It could be concluded the patient’s growth and development were considered to be in accordance with the baby’s stages of development. Therefore, the results of this study were in line with previous research and theories